2015
DOI: 10.1364/oe.23.004506
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the specular spectral reflectance of partially ordered alumina nanopores on an aluminum substrate

Abstract: Anodizing of aluminum generates a porous alumina layer comprising cylindrical nanopores (300 nm diameter) extending essentially perpendicular to the substrate. The pore distribution over the surface exhibits a short-distance order close to hexagonal arrangement. On the contrary, long-distance order cannot be defined: the arrangement is not periodic. Visual observation of such nanoporous layers shows a reddish specular reflectance consistent with reflectance spectrum measurements. This work is a parametric stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Experimental observations have demonstrated that the shape and size of a nanopore can deviate significantly from their expected value, 73 as the dimensions of a nanopore cannot be precisely determined through experimental observations. Furthermore, the size of the nanopores in the catalytic reactor has a substantial effect on the reactor performance as demonstrated at the end of the "Model Development" section.…”
Section: Uncertainty Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental observations have demonstrated that the shape and size of a nanopore can deviate significantly from their expected value, 73 as the dimensions of a nanopore cannot be precisely determined through experimental observations. Furthermore, the size of the nanopores in the catalytic reactor has a substantial effect on the reactor performance as demonstrated at the end of the "Model Development" section.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…73 The key kinetic parameters were assumed to follow the same normal distribution as described in the previous subsection. Figure 9 shows the effect of parameter uncertainties on the output species concentrations C out;i 0; L ð Þ determined using the primary multiscale reactor model and the second-order PSE.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Slight variations in PDA distribution and sample thickness in the experimental measurements are not accounted for in the determination of n and κ or the RCWA calculation, causing small differences in the spectra as a result. One important implication of the isotropic assumption is the emergence of interference effects in the calculation results, which manifest as oscillations in the spectra. This oscillatory behavior adds deviations which are not seen in the experimental results, due to the slight thickness variations, PDA distribution inhomogeneities, and surface roughnesses of the true samples. , It is also worth noting that the non-uniform nature of the OTP sample surfaces are similar to that of true skin surfaces . The calculated spectra are displayed as moving averages whereas the error is displayed as the peak envelope of the oscillating error function.…”
Section: Resultsmentioning
confidence: 99%
“…The elementary layer consists of a checkerboard layout with the square array of 10 × 10, and the center of each nanosphere locates at each intersection, that is, every elementary layer has 100 elementary cells. The statistical analysis utilizes the feature extraction to transform the elementary layer into a binary image [15,16], then the area and corresponding diameter of each nanosphere can be calculated. The key to build an elementary layer is to make the designed values of μ and σ coincide well with the experimental or desired values.…”
Section: Simulationmentioning
confidence: 99%
“…And the lattice spacing in x-z plane is set a fixed value of 1.5 μm. The minimum value or setting principle of lattice spacing should avoid the overlapping of nanospheres in models [15]. The layer number of elementary layer is also adjustable to match the observed morphology (figure 1(a)) with multilayer MoSe 2 nanospheres stacking.…”
Section: Simulationmentioning
confidence: 99%